Inverse Scattering Problem on the Axis for the Schrödinger Operator with Triangular 2 x 2 Matrix Potential. II. Addition of the Discrete Spectrum - Zubkova, E.I.; Rofe-Beketov, F.S. (Журнал математической физики, анализа, геометрии, 2007)
The theorem of the necessary and sufficient conditions for the solvability of ISP under consideration is proved. The method of addition of the discrete spectrum to the considered matrix not self-adjoint case is developed.